HER2-enriched subtype and pathological complete response in HER2-positive breast cancer: A systematic review and meta-analysis. (March 2020) - Schettini, Francesco; Pascual, Tomás; Conte, Benedetta; Chic, Nuria; Brasó-Maristany, Fara; Galván, Patricia; Martínez, Olga; Adamo, Barbara; Vidal, Maria; Muñoz, Montserrat; Fernández-Martinez, Aranzazu; Rognoni, Carla; et al.
Highlights: We correlated the breast cancer intrinsic subtypes with pCR in HER2+ disease. The HER2-E subtype was significantly and consistently associated with pCR after anti-HER2-based therapy. The HER2-E subtype was associated with pCR irrespective of hormone receptor status. The HER2-E subtype was associated with pCR also with chemo-free neoadjuvant schemes. Abstract: Background: HER2-positive (HER2+) breast cancer (BC) comprises all the four PAM50 molecular subtypes. Among these, the HER2-Enriched (HER2-E) appear to be associated with higher pathological complete response (pCR) rates following anti-HER2-based regimens. Here, we present a meta -analysis to validate the association of the HER2-E subtype with pCR following anti-HER2-based neoadjuvant treatments with or without chemotherapy (CT). Methods: A systematic literature search was performed in February 2019. The primary objective was to compare the association between HER2-E subtype (versus others) and pCR. Selected secondary objectives were to compare the association between 1) HER2-E subtype and pCR in CT-free studies, 2) HER2-E subtype within hormone receptor (HR)-negative and HR+ disease and 3) HR-negative disease (versus HR+) and pCR in all patients and within HER2-E subtype. A random-effect model was applied. The Higgins' I 2 was used to quantify heterogeneity. Results: Sixteen studies were included, 5 of which tested CT-free regimens. HER2-E subtype was significantly associated with pCR in all patients (odds ratio [OR] = 3.50, p < 0.001, I 2  = 33%), in HR+ (OR = 3.61, p < 0.001, I 2  = 1%) and HR-negative tumors (OR = 2.28, p = 0.01, I 2  = 47%). In CT-free studies, HER2-E subtype was associated with pCR in all patients (OR = 5.52, p < 0.001, I 2  = 0%) and in HR + disease (OR = 4.08, p = 0.001, I 2  = 0%). HR-negative status was significantly associated with pCR compared to HR + status in all patients (OR = 2.41, p < 0.001, I 2  = 30%) and within the HER2-E subtype (OR = 1.76, p < 0.001, I 2  = 0%). Conclusions: The HER2-E biomarker identifies patients with a higher likelihood of achieving a pCR following neoadjuvant anti-HER2-based therapy beyond HR status and CT use. Future trial designs to escalate or de-escalate systemic therapy in HER2+ disease should consider this genomic biomarker.